2019
DOI: 10.1111/iju.13931
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor 1 sustained‐release collagen on urethral catheter prevents stricture after urethral injury in a rabbit model

Abstract: Objectives To evaluate the preventive effect of an insulin‐like growth factor 1 sustained‐release collagen urethral catheter on urethral stricture after urethral injury in a rabbit model. Methods We made urethral catheters coated either with insulin‐like growth factor 1 impregnated collagen or with only collagen, and we divided 19 male Japanese white rabbits into three groups according to the kind of catheter inserted immediately after the rabbit's urethra was injured by electrocoagulation. Group 1 (n = 7) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The current mitotic drugs used in anti-scar treatment are steroid drugs and antitumor drugs including docetaxel, corticosteroid, 5-fluorouracil, bleomycin, mitomycin C, and retinoic acid. 22 Previous studies showed that drugs targeting anti-inflammatory and anti-cell proliferation may be ideal candidates for stent-based therapy to prevent restenosis. 23 Kim et al 24 revealed significantly less granulation tissue formation at both time points in the rats receiving sirolimus-eluting biodegradable PLLA stent by urethrographic and histologic examinations.…”
Section: Resultsmentioning
confidence: 99%
“…The current mitotic drugs used in anti-scar treatment are steroid drugs and antitumor drugs including docetaxel, corticosteroid, 5-fluorouracil, bleomycin, mitomycin C, and retinoic acid. 22 Previous studies showed that drugs targeting anti-inflammatory and anti-cell proliferation may be ideal candidates for stent-based therapy to prevent restenosis. 23 Kim et al 24 revealed significantly less granulation tissue formation at both time points in the rats receiving sirolimus-eluting biodegradable PLLA stent by urethrographic and histologic examinations.…”
Section: Resultsmentioning
confidence: 99%
“…We followed the method reported by Shinchi et al. [ 5 ] and successfully formed strictures. TGP-encapsulated cell transplantation was performed without hurdles.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). The urethra was injured by electrocoagulation with spherical monopolar electrocautery, wherein a spherical electrode was inserted into the bulbar urethra from the external urethral meatus and used for 30 s of electrocoagulation at 40 W [ 5 ]. Retrograde urethrography and urethroscopy observations were carried out to confirm the injured urethral segments immediately and after 14 days to confirm the stricture's creation ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study results reported that IGF-1 promotes the wound healing of skin ulcers in diabetic rats [114]. Shinchi et al revealed in a rabbit model that IGF-1 may sustain the collagen release and significantly improves the wound healing and may prevent the urethral stricture after urethral injury [115]. IGF-1 has a therapeutic effect even in the healing of gingival mucosa damage [116].…”
Section: Insulin-like Growth Factor Family and Wound Healingmentioning
confidence: 99%